2020
DOI: 10.1155/2020/7126976
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide Inhibits Glioma Cells by Increasing Oxidative Stress via the miRNA-338-5p Regulation of Hedgehog Signaling

Abstract: Objective. Chidamide has a broad spectrum of antitumor activity but its function on glioma remains unknown. The increase of reactive oxygen species (ROS) and reactive nitrogen species (RNS) may control glioma risk by promoting its apoptosis and necrosis. Hedgehog pathway is crucial to glioma cell proliferation and controls ROS production. We aimed to explore the effects of chidamide on the levels of miR-338-5p (glioma cell inhibitor), which may regulate Hedgehog signaling, resulting in the changes of RNS. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“… 36 , 37 An imbalance between the production of ROS and cells antioxidant system’s ability to readily detoxify ROS, results in oxidative stress. 38 , 39 It was shown that ROS released during quercetin and chloroquine administration resulted in caspase activation which was particularly involved in the survival of glioma cells. 40 In addition, mitochondria-mediated apoptosis was accompanied by BAX mitochondrial distribution and oligomerization, and caspase 3/caspase 8/caspase 9 activation.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 An imbalance between the production of ROS and cells antioxidant system’s ability to readily detoxify ROS, results in oxidative stress. 38 , 39 It was shown that ROS released during quercetin and chloroquine administration resulted in caspase activation which was particularly involved in the survival of glioma cells. 40 In addition, mitochondria-mediated apoptosis was accompanied by BAX mitochondrial distribution and oligomerization, and caspase 3/caspase 8/caspase 9 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that oxidative stress state exhibited an inhibitory effect on the pathological process of tumors. For example, miRNA-338-5p promotes oxidative stress by regulating the Hedgehog pathway and ultimately inhibited the proliferation of gliomas [11]. Moreover, inducing oxidative stress of C6 glioma cells was related with the promotion of cell cycle arrest and apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, CDM inhibits the proliferation of glioma cells, lung cancer, pancreatic cancer, and myeloma cells [24][25][26]. In Jurkat and HUT-78 cells, treatment with CDM (2 ÎźM) leads to downregulation of HDAC3 expression, thus inducing necroptosis [27].…”
Section: Discussionmentioning
confidence: 83%